The Effectiveness of Powtoon Animated Media in Improving Early Reading Skills Among Second-Grade Students - Radia Rahma; Kadek Hariana; Muhammad Fasli; Yun Ratna Lagandesa; Surahman Wilade (Papanda Publisher, 2026)
Early literacy acquisition remains challenging in Indonesian elementary schools where conventional teaching methods predominate. This study investigated the effectiveness of Powtoon-based animated image media in enhancing initial reading abilities among second-grade students. Employing classroom action research methodology, the study involved 25 students at SD Inpres Bumi Sagu across two intervention cycles during August 2025. Data were collected through pre-tests, post-tests, structured observations, and interviews. Quantitative analysis calculated individual absorption capacity, classical learning completeness, and classical absorption capacity, while qualitative data underwent thematic analysis. Findings demonstrated substantial improvements across intervention cycles. Classical completeness increased from 36% (pre-action) to 64% (Cycle I) and 84% (Cycle II), while mean reading scores advanced from 63.2 to 68.0 and finally 76.0. Teacher activity observations progressed from 75.75% to 85% (very good category), and student engagement increased from 70% to 81.25% (very good category). Qualitative observations revealed heightened motivation, sustained attention, and 92% student preference for animated instruction. Unexpectedly, students with stronger phonemic awareness foundations exhibited greater gains than those with severe literacy deficits. Results support cognitive theory of multimedia learning, demonstrating that animated media enhances literacy outcomes through dual-channel processing while improving engagement. The intervention proves effective as an enhancement tool requiring strategic integration with explicit phonics instruction for struggling readers.